Зв’язок між удоєм корів і їх ростом в онтогенезі за різної тривалості молочного періоду - Милостивий, Роман Васильович; Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman; Надрага, Микола Михайлович; Nadraha, Mykola; Новокшонова, Галина Корніївна; Novokshonova, Halyna (Дніпровський ДАЕУ, 2018)
Висвітлено експериментальні дані досліджень щодо зв’язку між молочною продуктивністю корів голштинської породи та їх енергією росту в онтогенезі. Встановлено, що за швидкої енергії росту спостерігається позитивний зв’язок із довічною продуктивністю тварин уже в ранні періоди розвитку (r=0,17-0,34; R2=2,9-14,5 %), в той час як за низьких приростів, про довічну продуктивність корів можна судити лише на пізніх стадіях онтогенезу (r=0,71-0,98; R2=1,4-96,3 %). За промислової технології виробництва молока виявлено позитивний зв’язок (r=0,33-0,39) між довічною продуктивністю та швидкістю спаду росту в онтогенезі. Intensive management of the dairy cattle breeding industry is associated with a reduction in the useful life of livestock. Therefore, getting a healthy heifer remains an important point in the system of effective work of a dairy enterprise. It is known that the growth and development of the calf largely determines the future productivity of the dairy cow. Highly productive animals, as a rule, have a higher energy of growth and a living mass in ontogenesis, so this is important for selection. However, unfavorable economic conditions force stockbreeders to reduce dairy feed for calves, in favor of early consumption to concentrates. Inadequate consumption of milk can badly affect their health and productivity. The purpose of this study was to investigate the effect of the level of consumption of calf milk on the correlation between its growth and milk yield in the future. It was found that calves, who received more milk for a longer time, had higher body weight gain ‒ by 12.0‒22.6 % (P <0,01). This difference in the process of how animals grow decreased. Correlation-regression analysis showed that the relationship between live weight and milk yield, milk fat and protein in three lactations is low and medium, mostly negative. However, it was noted that with the intensive growth of calves, the correlation between the mass at the age of six months and the yield of milk for the entire productive life was rather high, respectively, r = 0.46; r = 0.41 and r = 0.40 (P <0,05). The coefficient of determination was 15.6‒21.6 %. Growth energy had a closer relationship with productivity than with the mass of calves in certain periods of ontogeny. It depended on the amount of milk eaten in different conditions in which animals were grown. With a rapid growth energy, a positive relationship with lifelong productivity of animals is observed already in the early periods of development (r = 0.17‒0.34, R2 = 2.9‒14.5 %). Low weight gain makes it possible to predict the level of cow productivity only in the late stages of ontogeny (r = 0.71‒0.98, R2 = 1.4‒96.3 %). In this study, it can be concluded that intensive growth during early ontogeny allows earlier evaluation of the yield of milk of the cow due to a closer correlation between these signs.
The relationship between milk yield of cows and their growth in ontogenesis depends on the duration of the period of milk intake
Keywords: корови; cows; голштинська порода; Holstein breed; молочна продуктивність; milk productivity; енергія росту; energy of growth; кореляція; correlation